The Effect of Spillover Foreign Direct Investment on Labor Productivity in Indonesia - Krismanti Tri Wahyuni; Anugerah Karta Monika; Robert Kurniawan; Yoga Dwi Nugroho; Rezzy Eko Caraka (Muhammadiyah University Press, 2022)
The contribution of the manufacturing sector to Indonesia’s GDP reaches more than 20 percent. However, Indonesia has challenges to increase the productivity of workers who work in the industrial sector. The Omnibus law requires the assistance of foreign workers to work in Indonesia so that technology and expertise transfer happen. Foreign workers are believed to have a spillover effect in the form of skills and technology transfer through Foreign Direct Investment (FDI). FDI in the manufacturing sector allows an increase in labor productivity as a result of the spillover effect in the form of the transfer of skills and technology. This study aims to examine the impact of FDI spillover by making a comparison between labor productivity in companies whose ownership is dominated by foreign and domestic. Using data used from a large medium industry survey in 2010-2014. The method used in this research is panel data regression analysis with a cross-section of 28 industry subcategories derived from ISIC and a 5-year time series from 2010-2014, when the manufacturing sector became a source of growth in Indonesia of more than one percent. The results are in general FDI has a positive effect on labor productivity in companies whose ownership is dominated by foreign and domestic ownership. Meanwhile, FDI spillovers on labor productivity did not occur in companies whose ownership was dominated by domestic but occurred in companies whose ownership was dominated by foreigners.